Integrating Machine Translation with Human Translation in the Age of Artificial Intelligence: Challenges and Opportunities - Jiang, Kai; Lu, Xi (Big Data Analytics for Cyber-Physical System in Smart City, 2021)
Driven by the rise of new technologies such as big data, Internet of Things, and voice recognition, artificial intelligence has accelerated its progress in deep learning and human-machine collaboration. The advance in artificial intelligence has brought significant changes to the society. In the field of translation, the rapid emergence of internet translation tools poses potential challenges to professional translators. Meanwhile, it also brings unprecedented opportunities to the industry. This paper first reviews and summarizes the development of machine translation in China. Then, it analyzes the potential impact of artificial intelligence on the translation industry, and the competition and complementarity between machine translation and human translation. At last, the paper discusses the integration of machine translation with human translation, and visualizes the future prospect of translation technology, hoping to give reference to translators and translation researchers.